Cysteine-modified silica resin in DGT samplers for mercury and trace metals assessment - Reichstädter, Marek; Gao, Yue; Diviš, Pavel; Ma, Tianhui; Gaulier, Camille; Leermakers, Martine (Chemosphere, 2021)
Diffusive gradients in thin-films (DGT) is an in situ passive sampling technique to assess labile trace metal concentrations in different environmental matrix. The technique is consisting of a diffusive domain backed up by a resin gel that binds free metals and metal complexes that dissociate in the diffusive domain. This technique requires specific resin for special metals, for example mercury (Hg), since the classic resin (Chelex-100) gel is not applicable for Hg measurement. A simultaneous determination of Hg with other metals by the DGT was not yet reported. Two biomolecule-based resins were prepared by glutaraldehyde immobilisation of cysteine onto 3-amino-functionalised silica and 3-aminopropyl-functionalised silica, respectively. The load of functional groups on modified resins was qualitatively and quantitatively characterised. The modified resins were applied in the DGT technique and the uptake efficiency, elution efficiency, and linear accumulation of analytes of the DGT were tested. This novel DGT technique, using two cysteine-modified resins, can accumulate Hg and other metals in a broad range of pH and ionic strength in solutions. In the Belgian coastal zone (BCZ), the concentrations of Hg and other trace metals sampled by cysteine-modified resin-DGTs were similar as those by the other two DGT assemblies for Hg and other trace metals, respectively. The cysteine-modified silica resin combined the features of Chelex-100 resin and 3-mercaptopropyl silica resin and allowed simultaneous determination of labile Hg and other trace metals. The resin with a higher load of functional groups also showed higher performance in the further application in the DGT technique.
Keywords: Mercury; oxid křemičitý; Environmental Monitoring; Water Pollutants, Chemical; Belgian coastal zone; Diffusive gradients in thin-films; Silicon Dioxide; Trace metals; monitorování životního prostředí; difuze; Cysteine; Diffusion; rtuť; Immobilisation; chemické látky znečišťující vodu; cystein